Harapan terhadap Perdamaian: Peran Need for Closure, Fondasi Moral, dan Latar Belakang Demografis - Agus Abdul Rahman; Nur'aini Azizah; Royanulloh Royanulloh (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2020)
This study aims to examine the role of need for closure, moral foundations, and demographic background on hope for peace. The method used was a quantitative survey of 374 students. The measuring instrument consisted of a scale of hope in the context of peace, a scale of need for closure (NFC), and a moral foundation questionnaire (MFQ). The measured demographic background includes age, gender, ethnicity, and affiliation of religious organizations. Data were analyzed using path analysis. Findings from this study indicate that need for closure and moral foundations have a significant direct effect on hopes for peace. There are no differences in hope for peace at different ages, genders, religious organizational affiliations, and ethnicities.